IMPLEMENTASI KEBIJAKAN ABSENSI ONLINE APARATUR SIPIL NEGARA DI KANTOR SEKRETARIAT DAERAH KABUPATEN POHUWATO - Rusni Djafar (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2025)
The aims of this research to examine the implementation of the online attendance policy for Civil Servants (ASN) at the Regional Secretariat Office of Pohuwato Regency. The research focuses on how the policy is executed, its alignment with organizational goals, and the challenges encountered. The findings reveal that the online attendance policy is strongly aligned with the objectives of improving employee discipline and efficiency as part of bureaucratic reform. Although policy information dissemination has been carried out, comprehension remains limited among field staff and senior employees. Additionally, the enforcement of attendance rules is inconsistent, leading to negative perceptions of fairness. Despite being technically feasible, implementation is hindered by system disruptions, poor network coverage, and insufficient technical skills. Enhancing socialization, ensuring fair rule enforcement, improving technical infrastructure, and establishing specific Standard Operating Procedures (SOPs) are necessary to improve policy effectiveness. Violations of the policy may affect the payment of additional income allowances